High-performance Si/nano-Cu/CNTs/C anode derived from photovoltaic silicon waste: A potential photovoltaic-energy storage strategy. (June 2021) - Zhang, Zhao; Xi, Fengshuo; Li, Shaoyuan; Wan, Xiaohan; Ma, Wenhui; Chen, Xiuhua; Chen, Zhengjie; Deng, Rong; Ji, Jingjia; Fan, Hua-Jun; Chong, CheeMun
Abstract: The growing photovoltaic industry produces a mass of silicon cutting waste each year. How to effectively manage the resulting silicon cutting waste is essential from an environmental and an economic perspective. In this study, a new strategy was developed to utilize silicon cutting waste and fabricate high-performance lithium-ion battery anode materials. This study combines nanocopper-assisted chemical etching technology with graphite and carbon nanotubes (CNTs) coating technology. The resulting Si/nano-Cu/CNTs/C composite show an excellent reversible capacity of 1750 mAh/g and 64% capacity retention rate after 100 cycles at 200 mA/g. Different current charging and discharging tests were applied, and good rate performance achieved. When the current was switched from 2000 mA/g to 100 mA/g, the discharge capacity returned to the original 1750 mAh/g, demonstrating excellent rate performance. Furthermore, the higher ion diffusion coefficient improved the conductivity of the electrode, and the combination of silicon and carbon is beneficial to the electrode stability, which was verified by simulation calculation. Our work indicates that the silicon waste can be a cost-effective silicon source in the preparation of high-performance Si/C anode material by the simple and economical manufacturing method. Graphical abstract: Image 1 Highlights: Photovoltaic cutting waste was expected to achieve high value-added utilization in LIBs anodes. The pSi/nano-Cu/CNTS/C was synthesized by simple and effective composite process. The pSi/nano-Cu/CNTS/C composite exhibits an excellent electrochemical performance.